ANALISIS EFEKTITAS KEBIJAKAN PUBLIK DALAM UPAYA PERBERDAYAAN MASYARAKAT, DI KECAMATAN KINTAMANI, KABUPATEN BANGLI. - Sedia, I Wayan (Jurnal Widya Publika, 2021)
This study aims to determine the main factors that hinder community empowerment and the efforts made by local governments and the importance of applying local wisdom such as the values ​​contained in Tat Twam Asi, in reducing poverty in Kintamani. This research used interview and observation method, then the data found were analyzed and presented descriptively. From the results of the study, it was found that Bangli local government policies, culture and local wisdom greatly influenced efforts to empower and alleviate poverty in Kintamani. Regional policies that are inappropriate and conflict with local needs and traditions are the main factors that hinder efforts to reduce poverty in Kintamani. Likewise, the traditions of society are difficult to change following the developments and dynamics of the times